Hubungan Pelayanan Keperawatan Mahasiswa Praktik Dengan Tingkat Kepuasan Lansia di PPSLU Cilacap - Sholehah, Fitri Deniyati; Hikmawati, Isna (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Nursing services are professional services as an integral part of health services based on nursing knowledge and tips. As a profession, the services provided must be professional, so nurses must have competence and meet nursing practice standards. Nursing services affect positively on the satisfaction of the elderly in social institutions.Objectives: To find out the services provided by nursing students S1 program of Universitas Muhammadiyah Purwokerto during clinical practice with the level of elderly satisfaction at PPSLU Cilacap.Method: This is a quantitative descriptive correlation design using cross sectional approach. The sample of this study is the elderly in PPSLU Cilacap with a total of 50 respondents using the Consecutive sampling method in December 2019. Chi Square test was used as the questionnaire research instrument.Results: The results of the study show that the most respondents are female (52.0%), the most marital status is widowed (32.0%), and their health conditions are mostly sick 56.0%. There is a correlation between nursing students during their clinical practice and the satisfaction level of elderly at PPSLU Cilacap with the p value = 0.030 and OR value 3,611.Conclusion: There is a correlation between nursing students during their clinical practice and Elderly Satisfaction Level at PPSLU Cilacap with value (p value = 0.030) and OR value 3,611. Therefore, the more appropriate the nursing services provided means the higher the satisfaction level.Keywords: nursing service, student practice, satisfaction, elderlyÂ Â